LOCAL TAX AND RETRIBUTION REGULATIONS AFTER PDRD LAW’S TRANSITION TO HKPD LAW - Afifulloh; Tunggul Anshari Setia Negara; Shinta Hadiyantina (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
As a decentralized country, Indonesia grants each area governmental autonomy. For their development, local governments generally use the increase in Local Own-source Revenue (PAD), Fiscal Balance, and Other Lawful Local Revenue (LPDS). As stated in the laws, the rise in PAD comes from local taxes and retribution, local asset management, and other lawful local revenue. In early 2022, the Government issued Law Number 1 Year 2022 regarding Financial Relations between the Central and Regional Government to replace the decade-long Law Number 28 Year 2009 regarding Local Taxes and Retribution. This transition was considered after fiscal issues found in recent years and will affect local tax and retribution regulations’ schemes, rate percentages, and types as it was anticipated.